Persepsi dan Partisipasi Masyarakat dalam Pengelolaan Kawasan Tambang Pasir Bandar Batauga - Tri Astuti; Jaudin Jaudin; Nurlita Pertiwi; Husnah Katjina; Hasni Hasni (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
This study aims to examine public perceptions and participation in the management of sand mining in Bandar Batauga Village, Batauga District, South Buton Regency with a qualitative approach. The research location is in Bandar Batauga Village. The study was conducted in June 2021. The research population was the people of Bandar Batauga, while the research sample was 50 respondents using a purposive sampling technique. Data was collected by means of observation and questionnaires. Data analysis was carried out in a qualitative descriptive manner. The results showed that the majority of respondents agreed that sand mining activities had damaged the environment so that additional efforts were needed for sand mining management and the role of the Regional Government was needed to participate in preserving the environment. However, this sand mining activity is still needed by the residents. The largest community participation in the management of sand mining is provided through the provision of advice and input regarding better sand mining management, followed by warnings that sand mining activities will pose a danger and have a negative impact on the environment.